Downslope variation in hemipelagic sedimentation in an active margin basin: An example from the lower Pleistocene Kiwada and Takamizo formations on the Boso Peninsula, Japan. Issue 3 (29th November 2022) - Kurosawa, Shiho; Furota, Satoshi; Mitsui, Mayu; Sawada, Ken; Seike, Koji; Furukawa, Noboru; Ito, Makoto
Abstract: Hemipelagites are widespread fine‐grained sediments found from shelf margin to deep‐water environments, and they are considered to have been formed as background sedimentation by vertical settling and slow lateral advection of clastic and biogenic fine‐grained particles. Downflow variation in hemipelagic sedimentation, however, is not yet clearly understood, and was investigated in the lower Pleistocene Kiwada and Takamizo formations in the Kazusa forearc basin on the Boso Peninsula, Japan. Mapping of three tephra key beds enabled detailed correlation of two hemipelagite beds over a distance of ca 30 km from shelf‐margin to basin‐plain environments. The sedimentation rates decreased gradually in the downslope direction, but increased locally in response to turbidite sedimentation. This downslope variation indicates that hemipelagic sedimentation is not necessarily constant and varies in response to progradation and retrogradation of deep‐water depositional systems, as well as additional input of fine‐grained sediments from turbidity currents. In contrast, the grain size, magnetic susceptibility, clay‐mineral composition, total organic carbon contents relative to total nitrogen contents (carbon/nitrogen), and δ 13 C values of organic carbon do not exhibit distinct downslope variation. This downslope consistency indicates that hemipelagites document temporal perturbations of geological and palaeoclimatic conditions in hinterlands, regardless of spatial and temporal variations in deep‐water depositional environments. The concentrations of total organic carbon, total nitrogen and five biomarkers were lower values in turbiditic mudstones and hemipelagites that formed above a turbidite bed than in those of the other hemipelagites. This variation suggests that an additional supply of fine‐grained sediments from turbidity currents likely diluted the organic matter in the hemipelagites. In addition, hemipelagites for which deposition was affected by turbidity currents exhibit slightly lower δ 13 C values, and may also document an additional contribution of terrestrial organic matter from turbidity currents.